2020
DOI: 10.3390/su12041627
|View full text |Cite
|
Sign up to set email alerts
|

Corn and Rice Cultivation Affect Soil Organic and Inorganic Carbon Storage through Altering Soil Properties in Alkali Sodic Soils, Northeast of China

Abstract: Soil organic carbon (SOC) and soil inorganic carbon (SIC) play essential roles in carbon cycling in terrestrial ecosystems; however, the effects of crop cultivation on them are still poorly understood, especially in alkali sodic soils widely distributed in semiarid regions. Alkali sodic soils from cornfields and paddies with cultivation years of 5, 15, and 25 were analyzed here to assess the response of soil properties and soil carbon pools to crop cultivation. Soil pH and exchangeable sodium percentages decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Soda saline-alkali soil is the dominant type of soil in the region, and the major anions present are CO 3 2− and HCO 3 − [16]. The area was covered with native degraded grass vegetation (Leymus chinensis) before cultivation, without any prior cultivation or fertilization [17].…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…Soda saline-alkali soil is the dominant type of soil in the region, and the major anions present are CO 3 2− and HCO 3 − [16]. The area was covered with native degraded grass vegetation (Leymus chinensis) before cultivation, without any prior cultivation or fertilization [17].…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…On the other hand, this might be attributed to the developed maize root system in the surface soil, for it releases large amounts of enzymes via metabolism [3]. In our previous studies, we have observed decreasing enzyme activities followed by increasing soil alkaline status and long-term maize cultivation [39]. However, no obvious relationships or significant increases or decreases in enzyme activity in aggregates following oil sodic-alkali status were detected among fields.…”
Section: C-and N-cycling Enzymes In Soil Aggregatesmentioning
confidence: 74%
“…Our previous studies have found that maize cultivation in sodic-alkali soils has significantly improved soil physical-chemical properties, enriching SOC content and increasing enzyme activities [39]. Soil enzymes showed positive relationships with SOC storage, where INV and CAT were closely related to SOC in the studied areas [39].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation